"Even when it was hard, you pushed us to improve": Emotions and teacher learning in coaching conversations. (January 2023) - Schneeberger McGugan, Katherine; Horn, Ilana Seidel; Garner, Brette; Marshall, Samantha A.
Abstract: We investigate the role of teachers' edge-emotions in coaching conversations. While emotions are common in instructional coaching, they are under-examined in research. This qualitative study examines a particularly emotional coaching event that we facilitated with an experienced mathematics teacher. We use Kerdeman's (2003) framework of being "pulled up short" to describe how the teacher's understanding of her lesson was interrupted, resulting in negative emotions. She was ultimately motivated to transform her practice with our empathy and sustained support. We discuss implications for instructional coaching, particularly how edge-emotions can be leveraged to support teachers' conceptual change.